Network Analysis of the Relationship between Personality Traits and Online Behaviour in Adolescents and Young Adults: A Research on Dota 2 Players - O.V. Rubtsova; S.L. Artemenkov; A.S. Panfilova; A.M. Tokarchuk (Moscow State University of Psychology and Education, 2023)
The article presents the results of a correlation analysis of the influence of Dota-2 players’ personal characteristics on their behavior in the virtual space. The analysis is based on the data, received in the course of a series of experiments conducted by the Center for Interdisciplinary Research on Contemporary Childhood in Moscow State University of Psychology and Education in 2015-2023. Research methods include the Q-Sort technique by W. Stephenson, the Butler-Haigh “Real and Ideal Test”, the Role Conflict Questionnaire developed by O.V. Rubtsova, and Adolescent Egocentrism Scale (AES) by R. Enright. The sample includes 103 active players of MOBA Dota-2 aged 14—25. The paper discusses statistical correlations, in particular, those identified on the basis of a network analysis of partial correlations. The analysis suggests that such factors as role incompatibility and the need for role-playing experience may be manifested in virtual play activity and partly determine the specifics of its implementation by adolescents and young adults.